Malignant Melanoma of the Palate: Report of a Metastatic Case - B. Cruz-Ordinario, Mel Valerie; Dg. Boado, Carlo Antonio; Gorospe, Agnes E (Asian Pacific Journal of Cancer Care, 2022)
Primary malignant melanoma of the oral cavity is a rare malignancy with an incidence of 0.2 to 8% of all melanomas. Melanoma arises from the malignant transformation of the melanocyte and cutaneous melanomas are the most common followed by ocular, mucosal and melanoma of unknown primary site. Here we present a case of a 54 year old male who presented with a pigmented lesion on the palate, a type of mucosal melanoma. Due to the rarity of this disease, it is infrequently studied. Hence, epidemiology, etiology, pathogenesis and prognosis still remains to be less understood than cutaneous melanoma. Early diagnosis is warranted as therapeutic options are limited for advanced and metastatic disease. Surgery is the primary therapeutic management and complete resection is the main goal. If not feasible, radiotherapy may also be employed to achieve local control and enhance locoregional response. Prognosis is generally poor for metastatic disease and there are no guidelines yet on the use of systemic therapy.